2003
DOI: 10.1101/gad.259003
|View full text |Cite
|
Sign up to set email alerts
|

The Sox9 transcription factor determines glial fate choice in the developing spinal cord

Abstract: The mechanism that causes neural stem cells in the central nervous system to switch from neurogenesis to gliogenesis is poorly understood. Here we analyzed spinal cord development of mice in which the transcription factor Sox9 was specifically ablated from neural stem cells by the CRE/loxP recombination system. These mice exhibit defects in the specification of oligodendrocytes and astrocytes, the two main types of glial cells in the central nervous system. Accompanying an early dramatic reduction in progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
616
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 586 publications
(644 citation statements)
references
References 36 publications
26
616
0
2
Order By: Relevance
“…In contrast, simultaneous introduction of Olig1 and Olig2 substantially increased the proportion of NG2 or PDGFRa positive OPCs. Consistent with this in vivo finding, overexpression of Olig1 and Olig2 in cultured GPCs increased the expression of Sox9, which plays an important role in OL fate choice in the developing spinal cord (Stolt et al, 2003), whereas Olig1 did not change Sox9 expression. These findings suggest that Olig2 expression can promote the extent of OL specification in the injured adult spinal cord as it does during development.…”
Section: Olig1 and Olig2 Cooperatively Regulate The Differentiation Osupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, simultaneous introduction of Olig1 and Olig2 substantially increased the proportion of NG2 or PDGFRa positive OPCs. Consistent with this in vivo finding, overexpression of Olig1 and Olig2 in cultured GPCs increased the expression of Sox9, which plays an important role in OL fate choice in the developing spinal cord (Stolt et al, 2003), whereas Olig1 did not change Sox9 expression. These findings suggest that Olig2 expression can promote the extent of OL specification in the injured adult spinal cord as it does during development.…”
Section: Olig1 and Olig2 Cooperatively Regulate The Differentiation Osupporting
confidence: 83%
“…Sox9 and Sox10 are two highly related group E Sox proteins, and both are implicated in OL development, but at different stages. Sox9 is known to exert a strong influence on the initial specification of OLs (Stolt et al, 2003), whereas Sox10 plays a key role in promoting terminal OL differentiation (Li et al, 2007a;Stolt et al, 2002). We found that overexpression of Olig1 and Olig2 resulted in a significant increase in Sox9 expression (P < 0.05 vs. GFP group and P < 0.01 vs. Olig1 group) (Fig.…”
Section: Changes In the Expression Of Ol-lineage Related Transcriptiomentioning
confidence: 59%
“…Previous studies in rodents showed that Id3 is only expressed in developing astrocytes (Lamantia, Tremblay, & Majewska, 2014; Molofsky et al, 2013). Sox9 is initially (E8.5–E18.5) expressed in all glial (precursor) cells, and is subsequently downregulated in myelinating oligodendrocytes (Stolt et al, 2003) and becomes astrocyte‐specific (Sun et al, 2017). Also NFIA is initially (E11.5) expressed in all developing glial cells, but downregulates Olig2 and becomes exclusive to astrocytes at E13.5–E16.5 (Deneen et al, 2006; Molofsky et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Expression studies have shown that SOX9 is expressed by neuroepithelial cells in the ventricular zone of the developing spinal cord, by oligodendrocytes and by astrocytes but not by neurons (Stolt et al, 2003). Knocking out Sox9 in the developing mouse spinal cord results in perinatal lethality, decreased numbers of oligodendrocyte progenitors and astrocytes and an increased number of motor neurons (Stolt et al, 2003) and neuroblasts (Scott et al, 2010).…”
Section: Discussionmentioning
confidence: 99%